Toll-like receptor and matrix metalloproteinase single-nucleotide polymorphisms, haplotypes, and polygenic risk score differentiated between tuberculosis disease and infection. (December 2022) - Lee, Meng-Rui; Chen, Yen-Lin; Wu, Chang-Wei; Chen, Lun-Che; Chang, Lih-Yu; Chen, Jung-Yueh; Huang, Yu-Tsung; Wang, Jann-Yuan; Shih, Jin-Yuan; Yu, Chong-Jen
Highlights: Toll-like receptor (TLR) 2 rs3804100 polymorphisms were associated with tuberculosis (TB) disease status. TLR1 and matrix metalloproteinase 8 single-nucleotide polymorphisms (SNP) variants also differed among latent TB infection and active TB. TLR1 and matrix metalloproteinase 12 haplotypes were associated with TB risk. A 3 single-nucleotide polymorphism (rs5743580, rs3804100, rs2508383) polygenic risk score helps predict TB status progression. Abstract: Objectives: The association of toll-like receptors (TLRs) and matrix metalloproteinases (MMPs) single-nucleotide polymorphisms (SNPs) among latent tuberculosis (TB) infection and active TB remained less studied. Methods: We recruited participants with TB disease (active TB) (n = 400) and TB infection (latent TB infection) (n = 203) in this study. We genotyped SNPs in TLR1, TLR2, TLR4, MMP1, MMP8, MMP9, MMP12, and tissue inhibitor of MMP2. Single-variant analysis and haplotype analysis were performed, and a polygenic risk score (PRS) was created. Results: We found that SNPs in TLR1 (rs5743580, rs5743551), TLR2 (rs3804100), and MMP8 (rs2508383) were associated with different TB disease status risks. TLR1 rs5743580 was associated with a higher risk of TB disease status in genotypic, recessive, and additive models. TLR2 rs3804100 polymorphisms demonstrated significant association with TB disease status in genotypic, dominant, and additive models. In the haplotype analysis, the TLR1 haplotype was associated with a higher risk of TB disease, and the MMP12 haplotype was associated with a lower risk of TB disease. A PRS using 3 SNPs was associated with a higher risk of TB disease. Conclusion: This study revealed that SNP variants in TLR1, TLR2, and MMP8 differed among TB infection and disease. Haplotypes and PRS could potentially help predict TB disease status. Graphical Abstract: Image, graphical abstract